CHARACTERIZATION AND MPLECLAR DETECTION OF PURIFIED PROTEUS MIRABILIS PMBS41 ALPHA-HEMOLYSIN - Essam Al-Jumaily; Sara Zgaer (Basrah Journal of Veterinary Research)
The Alpha- hemolysin, produced by Proteus mirabilis PMBS41 grown in a chemical definedmedium was purified 9.77 fold with a yield (14.90 %) . Alpha-hemolysin was estimate themolecular weight which was shown to be 88,750KD by using gel filtration chromatography usingSepharose -6B and 109.64 KD by using SDS-electrophoresis and exhibited an optimum temperatureof 35 and 40°C, and pH optimas at 8.0. Whereas hemolysin reserve a full of its activity at a pH 8and a temperature at 25° - 30°C.Molecular dectection was done by using specific primer to eachHpmA and HpmB genes that encode for Hemolysin as a virulence factor of proteus mirabilis byusing MPCR and electrophoresis technique.The PCR assay results identified (53) isolate possessed hpmA and hpmB genes of the proteusmirabilis bacteria diagnosed , This explains the blood analysis of all pathogenic bacterial isolates butwith different ratio and the importance of PCR in detection of virulence of proteus mirabilis inclinical urine samples of urinary tract infection (UTI) .